Marketing Communication as a Vital Element of the Internationalization Process - Drzazga, Jolanta (Komunikacja marketingowa jako ważny element w procesie internacjonalizacji, 2023)
The internationalisation of a company is a complex and multidimensional process that requires significant effort from every department. Nevertheless, it represents a tremendous opportunity to expand one’s business, which is why many companies decide to take this step. With globalisation and increased internet accessibility, there are now more ways to enter foreign markets than ever. To the extent that there are companies that are born global. Therefore, what factors influence the success of a company’s internationalisation process today? To find an answer and narrow the scope of the research, this article explores the role of marketing communication in this process. Furthermore, the research will analyse the example of creative organisations. Subsequently, in the empirical part, an analysis will be conducted based on a case study of the Polish cosmetics brand YOPE.
Drzazga, J. (2023). Marketing Communication as a Vital Element of the Internationalisation Process on the Example of YOPE. In A. Kuźmińska-Haberla, S. Bobowski (Eds.), Ekonomia i międzynarodowe stosunki gospodarcze (pp. 50-63). Wroclaw University of Economic and Business.
Keywords: internationalisation; creative organization; marketing communication; merchandising; internacjonalizacja; organizacja kreatywna; komunikacja marketingowa